THE BROTHERS AND SISTERS GROUP: A group for siblings of children with physical disabilities - Badger, Anne (Groupwork)
The group was created for the brothers and sisters of the disabled child in a family. The idea came from a growing recognition of the fact that social work resources are usually directed to the family member with the disability. Often the needs of the brothers and sisters are overlooked, and in most cases they face high expectations from their parents. The plan for this particular group was also influenced by the fact that two of the group leaders had disabled members in their families. The group was designed to give the children something for themselves, which they could attend without their disabled brother or sister; something which was reliable and consistent. A play environment was created in which the child could play and talk in large and small groups. It was also an environment in which feelings —sometimes hidden feelings—could be acknowledged and responded to.